Educational Prescriptions to Document Evidence-Based Medicine Questions in Ambulatory Care Advanced Pharmacy Practice Experiences - Philbrick, Ann M. (Am J Pharm Educ, 2019)
Objective. To design, implement, and assess the use of “educational prescriptions” or Education Rx assignments in advanced pharmacy practice experiences (APPEs) in ambulatory care, and to assess the impact of the assignments on Doctor of Pharmacy (PharmD) students’ self-efficacy to practice evidence-based medicine (EBM). Methods. Students enrolled in select ambulatory care APPEs completed up to four Education Rx assignments. The assignments required students to report the context of the question, source of information, results, appraisal of validity, and relevance of the evidence, and to answer the clinical question. A rubric was used that contained three subparts: a patient/population, intervention, comparison, outcome (PICO) conformity score (8 points), presence of answer to the PICO (1 point), and quality of answer to the PICO (6 points). Demographic information was collected and students were surveyed at the end of the APPE to rate their self-efficacy executing seven evidence-based medicine (EBM) skills. Results. Thirty students completed 110 Education Rxs. The average score (SD) was 13.6 (2.2) with a PICO conformity subsection score of 7.3 (1.3), and quality of answer subsection score of 5.3 (1.2). Only one Education Rx did not have an answer. Students consulted point-of-care references for a majority of the answers (65%). Sixteen (53%) students completed the self-assessment survey, and all strongly agreed or agreed that the Education Rx activity improved their ability to formulate a well-constructed clinical question and evaluate and apply the evidence. Conclusion. Through Education Rxs, PharmD students’ self-confidence and their skills in finding answers to clinical questions increased.